Lessons from the devastating impact of the first COVID-19 wave in Italy. (19th May 2021) - Anastassopoulou, Cleo; Siettos, Constantinos; Russo, Lucia; Vrioni, Georgia; Tsakris, Athanasios
ABSTRACT: Herein, we are critically examining the chain of events and discussing previously unrecognized factors that led to the 'perfect COVID-19 storm' in northern Italy during the first epidemic wave in spring 2020. SARS-CoV-2 was circulating uncontrollably at least for five weeks before the adoption of containment measures, and the role of exponential growth in the spread of the virus, conveyed by a high R 0, was likely underestimated. An understanding of this failure's causes and contexts will help us to control the strong second wave of the pandemic we are now facing in Europe, and to be better prepared for future outbreaks.